Таранний бій і "сарматська посадка" — коментар до праці Олександра Симоненка "Сарматские всадники Северного Причерноморья" - Гуцул, В.M. (Археологія і давня історія України, 2021)
У тексті дискутуються техніки бойового застосування списа сарматською кіннотою античної доби, відображені у візуальних джерелах. Автор зробив спробу інтерпретувати «баталістичну сарматську іконографію» за допомогою західноєвропейських фехтувальних трактатів XV—XVI ст. і висловив свої аргументи стосовно можливості / неможливості побутування кінного таранного бою і дворучного хвату списа в арсеналі сарматських мілітарних практик. The text discusses the techniques of combat use of the spear on horseback by the Sarmathian cavalry reflected in visual sources. The author attempts to interpret the «Sarmatian military iconography» on the base of Western European martial treatises of the XV—XVI centuries and expressed his arguments about the presence or absence of mounted shock combat and a spear’s two-handed grip in the Sarmatian military practices. In conclusion full discussion of the «Sarmatian seat» is based on an a priori statement that the Sarmatians possessed the technique of mounted shock combat. The historical sources do not confirm this thesis. Instea, if we assume that the Sarmatians used the riding horse primarily as means of transport on the battlefield (rather than as a means of radically increasing the power of the blow, as did the knights during shock attack), then various techniques of holding and using a spear, including two-handed grip, look quite possible, especially at low speeds of the horse. But they should not look at the «Sarmatian seat» for anything specifically Sarmatian, their battle tactics were based on the tactical and technical characteristics of the spear as a weapon. To master the military technology of mounted shock combat a range of conditions were required: widespread use of metal armor, specially bred and trained horses, the presence of a saddle of special design and stirrups, as well as specific rider skills, including special landing in this saddle in «long» stirrups, and, most importantly, the appropriate economic base and cultural background on which the horseman who practiced such military technology were able to improve on their experience and to transfer competencies to the next generation of military elites. Such conditions developed as a result of the long evolution of military technology and military culture, relatively late, in the middle of the eleventh century. not everywhere in Europe, but exclusively in the Franco-Norman area and led to the genesis of Western European chivalry. Whereas no nomadic culture, even in the Middle Ages, was able to adapt the technology of mounted shock combat.